Assessment of Knowledge and Awareness of Down syndrome in Ha’il City Community, KSA - Khalifa, Amany Mohammed; Aljohani, Shaima Saad; Alshammari, Fauziah Abdullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Down syndrome is a condition in which a person has an extra chromosome. Chromosomes are small “packages” of genes in the body. They determine how a baby’s body forms and functions as it grows during pregnancy and after birth. Typically, a baby is born with 46 chromosomes. Babies with Down syndrome have an extra copy of one of these chromosomes, chromosome 21. A medical term for having an extra copy of a chromosome is ‘trisomy.’ Down syndrome is also referred to as Trisomy 21. This extra copy changes how the baby’s body and brain develop, which can cause both mental and physical challenges for the baby. The aim: the present study builded the interest to assess the knowledge and awareness of definition, causes, symptoms, diagnosis, complication, and treatment of Down Syndrome ( DS ) in Hail City and tried to improve the false thoughts about this disease. Material: A cross-sectional survey was distributed throughout in Hail City between October 2021 to April 2022. An online questionnaire was designed. It included informed consent and 10 questions about the sociodemographic data and questions regarding signs, symptoms, complications and management about DS. It was distributed via various social media apps. Methods: SPSS for Windows v22.0 IBM Inc..SPSS for windows Rel 15.0 2006 Chicago Inc. Results: The result of the present study revealed that the overall level of awareness about Down syndrome was moderate (65.7 %). More Health education for public, online seminars and more research are needed to raise the public awareness and spotlight to patients suffering from this syndrome.